Identification and characterization of long non‐coding RNAs as competing endogenous RNAs in the cold stress response of Triticum aestivum - Lu, Q.; Xu, Q.; Guo, F.; Lv, Y.; Song, C.; Feng, M.; Yu, J.; Zhang, D.; Cang, J.; Whelan, J. (Plant biology (Stuttgart, Germany), 2020)
Long non‐coding RNAs (lncRNAs) play important roles in plant development and stress responses. MicroRNAs (miRNAs) are involved in transcriptional and post‐transcriptional gene regulation. It is not clear how lncRNA‐mediated plant responses to cold stress and how lncRNAs, miRNAs and target mRNAs cooperate subject to the competing endogenous RNA (ceRNA). We interpreted the function of lncRNAs in the winter wheat cultivar Dongnongdongmai 1 (Dn1). A total of 9970 putative lncRNAs were initially identified from three Dn1 lncRNA libraries (5 °C, −10 °C and −25 °C) using high‐throughput sequencing. Among the 14,626 genes detected via weighted gene co‐expression network analysis, 7435 lncRNAs were co‐expressed with 7191 mRNAs. We found six modules related to cold resistance in the lncRNA–mRNA weighted co‐expression network, and the functions of mRNAs were similar in each module. Antioxidant systems and hormones played important roles in low‐temperature responses. RNA sequencing analysis revealed that interactions between the 384 lncRNAs and 70 miRNAs were required for ceRNA activity. According to ceRNA activity, 225 lncRNAs, 60 miRNAs and 621 target mRNAs were involved in the regulatory networks of the cold stress response. Notably, a conserved region was found in the complementary regions of lncRNAs and miR164/408 but had reverse expression trends in the ceRNA network. Our results reveal possible roles of lncRNAs–mRNAs in the regulatory networks associated with tolerance to low temperature and provide useful information for more strategic use of genomic resources in wheat breeding.